Historik and Historiography in Lithuania in 1904–1915: The Period of Historiographical Manifestos? - Gieda, Aurelijus (Lietuvos istorijos studijos, 2015)
The first two decades in the Lithuanian historiography of the 20th century have been little studied. Even less attention has been paid to the theoretical-methodological standpoints and the theory of historiography of that time. Despite the above, this paper aims to show why the period of 1904–1915 is special for the development of Lithuanian historiography. Taking into account the historiographic sources, discussions and polemic as well as the quest for innovations in the science of history of that time, the approach based on the importance of the processes of the first decades of the 20th century in historiography is constructed: the processes dating to 1904–1915 were not a short and insignificant episode in Lithuanian historiography between the historiography of the national revival (the second half of the 19th century) and the science of history of the inter-war period characterized by a more rapid pace of progress. On the contrary, the article shows that the afore-mentioned period is a peculiar period of historiographical manifestos, witnessing, at least in the theoretical dimension, the fundamental paradigmatic breakthrough, even as regards the whole 20th century Lithuanian historiography in general. With the possibilities provided by the history of ideas, programmatic historiographic texts, reviews and polemic of the beginning of the 20th century are analyzed; they are used to show how a patriotically-oriented pragmatic historiography was replaced by a historicist-critical programme of historical research in Lithuania. The article focuses on several principal topics and problems: the importance, place, and role of historiographical manifestos in the processes of the science of history; it questions such a periodization of Lithuanian historiography where the period of 1904–1915 is lacking any peculiar characteristics and highlights. It shows that the sociopolitical and sociocultural breakthrough of the first decade of the 20th century in Lithuania created new conditions for cultural as well as intellectual activities. The article notes that the institutionalization of history had long remained an especially acute problem in Lithuania, which triggered various intellectual initiatives and discussions. The initiatives undertaken by a special society dedicated to the research of the history of Lithuania and the publishing of a special history-focused newspaper (1905) were accompanied by public discussions in which the establishment of a special society intended for the research of history was evaluated as an over-specialized undertaking with an insufficient orientation towards more general national interests (as a certain aftermath of these discussions, a more general-profile Lithuanian Scientific Society was founded in 1907). Nevertheless, the discussions nurtured the climate for broader intellectual undertakings, the so-called historiographical manifestos (the selected texts of Mykolas Biržiška, Augustinas Janulaitis, and Augustinas Voldemaras). The article focuses on an in-depth analysis of these manifestos, showing that the intensified theoretical and methodological quest in Lithuanian historiography and the theory of historiography should be moved to the beginning of the 20th century. If we agree with Arthur Danto (1924–2013) who called Modernism the Age of Manifestos, with the conclusions of this article in mind, we can, with no exaggeration, call the period of Lithuanian historiography of 1904–1915 the Period of Manifestos.